Paul and Christian Identity-Formation in John Chrysostom's Homilies De Laudibus Sancti Pauli Apostoli - De Wet, Chris L. (Journal of early Christian history, 2013)
The aim of this study is to investigate the dynamics between Paulinomorphism (becoming like Paul) and Christian identity-formation in John Chrysostom's (347-407 C.E.) De laudibus sancti Pauli apostoli. Chrysostom understands Christian identity-formation as a type of Paulinomorphism. The discursive operation of Paulinomorphism is most clearly manifested in Chrysostom's homilies De laudibus sancti Pauli apostoli, and operates by means of four interrelated discourses, namely: a) transformation and mimesis; b) virtue and masculinization; c) the zealotic, and; d) medicalization. The four discourses are delineated and critically discussed in this study.